Correlation study between sunspot and rainfall in Udaipur subregion - JAIN, RAJMAL; TRIPATHY, S.C. (MAUSAM, 1997)
ABSTRACT. The cross correlation among 102 years rainfall data in Udaipur subtropical region and sunspots show tpe influence of solar activity on the climatic conditions of Udaipur. The periodicity obtained using rainfall and other data sets. such as. water storage of Jaisamand lake and gauge measurements of two rivers. Jakham and Karmoi, are similar to the periodicity of sunspots, which indicates a relationship between rainfall and sunspot activity. A period of about 27% is found to deviate from normal rains in the form of flood. excess and deficit of rains in Udaipur sub-tropical region. The possible physical mechanisms to explain sun-weather relationship in astro-physical context are discussed.